Wireless sensor multimedia networks : architectures, protocols, and applications - Azim, Mohamed Mostafa A.; Jiang Xiaohong (CRC Press, 2016)
Wireless sensor networks (WSNs) are a special class of ad hoc network in which network nodes composed of tiny sensors pass data such as temperature, pressure, and humidity through the network to a central location. Wireless sensor multimedia networks (WSMNs) are a special category of WSNs in which the sensor nodes are small cameras and microphones that can send voice, image, or video data through the network. This book presents the latest advances and research in WSMN architecture, algorithms, and protocols. It explores the many benefits of WSMNs and the variety of applications in which they can be used--surveillance, traffic monitoring, advanced healthcare (blood pressure and heart rate monitoring), habitat monitoring, and localization services (finding missing children or wanted criminals). --